A Survey of Technologies Supporting Virtual Project Based Learning - Tolsby, Håkon; Nyvang, Tom; Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2002)
This paper describes a survey of technologies and to what extent they support virtual project based learning. The paper argues that a survey of learning technologies should be related to concrete learning tasks and processes. Problem oriented project pedagogy (POPP) is discussed, and a framework for evaluation is proposed where negotiation of meaning, coordination and resource management are identified as the key concepts in virtual project based learning. Three e-learning systems are selected for the survey, Virtual-U, Lotus Learningspace and Lotus Quickplace, as each system offers different strategies for e-learning. The paper concludes that virtual project based learning may benefit from facilities of all these systems.